Probing the strong electron-acceptor property of pyridine-appended 1, 2, 3-benzotriazole ligand in tris-homoleptic Ru(II) and Fe(II) complexes. (1st November 2022) - Pandey, Sharmila; Mandal, Tanmoy; Mandal, Sanajit Kumar
Graphical abstract: Two tris homoleptic Ru(II) and Fe(II) complexes, [M(BTZ-2P )3 ] 2+, of pyridine-benzotriazole ligand BTZ-2P were synthesized and well characterized via spectroscopic and crystallographic techniques. The photophysical and electrochemical properties of both the complexes were assessed. Experimental findings were supported by theoretical calculation. BTZ-2P ligand was demonstrated to possess an excellent π-acceptor property. Abstract: In order to probe the σ-donor/π-acceptor properties of the fused triazolo-based pyridine-appended bidentate ligand, 1-(pyridin-2-yl)-1H-benzo[d][1–3]triazole (BTZ-2P ), two discrete octahedral tris-homoleptic complexes, [Ru(BTZ-2P )3 ](PF6 )2 (1) and [Fe(BTZ-2P )3 ](ClO4 )2 (2 ) were synthesized and well characterized for the first time. Crystal structures of the complexes revealed the key geometrical parameters which highlighted the metal-ligand bonding characteristics in the complexes, especially the strong π-acceptor property of the ligand. The bonding with the BTZ-2P ligand resulted in simultaneous stabilization of the HOMO and destabilization of the LUMO of both the metal complexes, leading to anodic shift of the M II/III redox potential and blue shift of the MLCT band in absorption spectroscopy in comparison to their analogous Ru(II) and Fe(II) tris-bipyridine complexes. Experimental results and theoretical calculations confirmed that in addition to being a good σ-donor, the BTZ-2P ligand exhibits strong π-acceptor property as well compared to the classic 2, 2′-bipyridine ligand. This disclosure can have future implications in stabilizing low-valent transition metal complexes with the BTZ-2P ligand.